The Influence of School Supervisor Supervision and Teacher Discipline on Teacher Performance : A Case Study at SMP Subrayon 07 Rawapitu, Tulang Bawang Regency - David Ariswandy; Epi Parela; Senen Mustakim (Jurnal Ilmiah Manajemen Kesatuan, 2025)
School supervisors, as one of the key figures in educational development, are responsible for ensuring the smooth implementation of education and teaching in schools. Enhancing the quality of education and teaching in schools is not an easy task. As mandated by the Indonesian Minister of National Education Regulation No. 12 of 2007 concerning school supervisor standards, supervisors are obliged to carry out their supervisory duties in accordance with these regulations. Specifically, supervisory services, as one of their competencies, aim to foster cooperation among personnel so that everyone collectively moves towards achieving educational goals through their willingness to carry out their respective duties efficiently and effectively. Another factor influencing teacher performance at SMP Subrayon 07 Rawapitu, Tulang Bawang Regency, is teacher discipline. The school administration also plays a role in managing teachers to ensure compliance with all rules and norms established by the school, thereby promoting disciplined and effective teaching performance. However, a notable phenomenon at SMP Subrayon 07 Rawapitu is the tardiness of some teachers, indicating a decline in teacher discipline within the institution. Teacher performance and achievement reflect the outcomes achieved by individuals in fulfilling their assigned tasks, based on their competence, experience, dedication, and time management. This study employs a quantitative descriptive research approach, with 32 research respondents. The study examines three variables: two independent variables (X1 and X2) and one dependent variable (Y). The independent variables are School Supervisor Supervision (X1) and Teacher Discipline (X2), while the dependent variable is Teacher Performance (Y). Based on data analysis, the research findings confirm the following hypotheses: There is an influence of School Supervisor Supervision (X1) on Teacher Performance (Y), with an impact level of 49.9%. There is an influence of Teacher Discipline (X2) on Teacher Performance (Y), with an impact level of 38.8%. There is a combined influence of School Supervisor Supervision (X1) and Teacher Discipline (X2) on Teacher Performance (Y), with an impact level of 52.8%. Keywords: School Supervisor Supervision, Teacher Discipline, Teacher Performance